Characteristics of a saturated 18.9-nm tabletop laser operating at 5-Hz repetition rate - Larotonda, M. A., author; Luther, Bradley M., author; Wang, Yanting, author; Liu, Y., author; Alessi, David Alan, author; Berrill, Mark Allen, author; Dummer, A., author; Brizuela, Fernando, author; Menoni, Carmen S., author; Marconi, Mario Carlos, author; Shlyaptsev, Vyacheslav N., author; Dunn, James, author; et al. (Colorado State University. Libraries, 2004)
We report the characteristics of a saturated high-repetition rate Ni-like Mo laser at 18.9 nm. This table-top soft X-ray laser was pumped at a 5-Hz repetition rate by 8-ps 1-J optical laser pulses impinging at grazing incidence into a precreated Mo plasma. The variation of the laser output intensity as a function of the grazing incidence angle of the main pump beam is reported. The maximum laser output intensity was observed for an angle of 20°, at which we measured a small signal gain of 65 cm-1 and a gain-length product g × l > 15. Spatial coherence measurements resulting from a Young's double-slit interference experiment show the equivalent incoherent source diameter is about 11 μm. The peak spectral brightness is estimated to be of the order of 1 × 1024 photons s-1 mm-2 mrad-2 within 0.01% spectral bandwidth. This type of practical, small scale, high-repetition soft X-ray laser is of interest for many applications.
Keywords: grazing incidence pumping; high-repetition rate; nickel-like Mo; x-ray lasers